Getting some reality into debates about NBN FTTP - Eckermann , Robin (Journal of Telecommunications and the Digital Economy, 2019)
Sentiment about fibre-to-the-premises (FTTP) runs hot in Australia, fuelled by the NBN initiative for Australia’s next generation of broadband. Unfortunately most of the debate is ill-informed, focusing on plumbing rather than the uses to which the network may be put. The base of users subscribing to the higher speeds made possible by FTTP is limited right now, and much of their communication will be speed-limited by constraints outside of the NBN FTTP segment. In addition, a growing proportion of Australians choose to operate entirely on mobile connections. For all these reasons, the number of users who would benefit from FTTP in the short term is modest. The Coalition has proposed greater use of existing infrastructure – in particular, using fibre-to-the-node (FTTN)/DSL technology and potentially hybrid-fibre-coax (HFC) technology – to deliver an upgrade earlier and at lower cost. In the face of cost pressures, it is likely that the original 93% FTTP target would be adjusted with greater use of wireless and satellite technologies in rural areas and the use of copper for the final link in multi-dwelling complexes. More generally, there is no question that FTTN/DSL solutions can deliver good quality broadband, but further work will be needed to determine where this can be done cost-effectively. Similarly, with appropriate upgrades, HFC networks can deliver next-generation broadband speeds. When practical factors are taken into consideration, the gap between Labor and Coalition plans closes somewhat. Developing the best strategy for Australia needs to take cost into consideration, and there is scope for NBN Co to improve its performance in this area. Any major cost blowout would have significant ramifications for broadband users and use in Australia. If the rollout of FTTP is scaled back, users with a need may still get access on a user-pays principle – though the practicality of this has yet to be demonstrated. Widespread FTTP remains the right long-term goal for Australia, but the approach for getting there needs to be finessed.